Potential Development of the Indonesian Halal Industry - Muhammad Bayu Dwie Saputra; Novi Febriyanti (Universitas Negeri Surabaya, 2024)
Halal and haram is a fairly familiar topic regarding food and beverage products or services. However, currently many products do not include the halal logo on their products, and in the current era, many consumers prefer to consume those that already have the halal logo because the quality is guaranteed. The aim of this research is to look at the development of the halal industry in Indonesia, using qualitative research which is supported by data and previous research which is in line with the research to be carried out. The government has implemented several programs to support the successful development of the halal industry, because seeing Indonesia's potential regarding the halal industry is also very good, the government also sees this as an opportunity for the nation's economy. Currently, the government continues to try to support the halal industry in Indonesia with various efforts, one of which is through implementing a halal certification policy